Beyond Sight: Developing Inclusive Health-related Exercise for Visually Challenged Learners - Magwate, Novie Queen; Sandiego, Chiedel Joan G. (Asia Research Network Journal of Education, 2025)
This study aimed to develop an exercise routine for Visually Challenged (VC) learners and investigate their previous experiences and background in the field of Physical Education (PE in the Special Education (SPED) schools of lligan City. In this study, qualitative and quantitative methods were applied utilizing Input, Process, and Output framework. This study employed qualitative and quantitative research designs. The researcher utilized Likert Scale to evaluate the exercise routine and semi-structured questionnaire to gather information about the previous experiences of SPED teachers and VC learners in the field of PE. Findings indicate a strong positive validation from the five experts. The material or instrument being evaluated is perceived as clear, relevant, understandable, well- worded, concise, comprehensive in its coverage of study variables, and utilizes an appropriate measurement scale. The consistent "Agree" or "Strongly Agree" interpretations across all indicators suggest that the experts found the evaluated material or instrument to be of high quality in terms of clarity, relevance, understandability, wording, conciseness, coverage of variables, and appropriateness of the scale. The study concluded that the development of an exercise routine for visually challenged learners is a feasible and promising approach to address the accessibility gap in physical education. A systematic, iterative design process, incorporating stakeholder feedback, is essential for creating effective and relevant educational tools for VC learners. The exercise routine format has the potential to enhance the learning experience of VC learners by providing accessible and engaging auditory instruction.